Analisis Tingkat Kepuasan Konsumen Terhadap Kualitas Produk dan Jasa Pengiriman Wine Pada PT. PW - Prasetyo, Christian Febry; Satriawan, I Ketut; Sadyasmara , Cokorda Anom Bayu (Department of Agroindustrial Technology, Faculty of Agricultural Technology, Udayana University, 2024)
The purpose of this study was to determine the product and service attributes that are considered important by consumers, calculate the level of importance and performance to meet consumer satisfaction, and analyze the attributes that are prioritized to be improved based on the level of importance and consumer satisfaction at PT. PW. The study used a survey method and data analysis with the Importance Performance Analysis (IPA) method. The data obtained in the study came from distributing questionnaires to 38 respondents who were customers of PT. PW. The results showed that all product and service attributes were considered very important by consumers. The average value of the level of importance of product attributes was 3.71 (very important) and service attributes were 3.79 (very important). Overall, the average value of the product satisfaction level was 83.85% and the level of service satisfaction was 81.75%. Analysis of attributes that are the main priority to be improved on product attributes, namely wine color, wine volume size, wine benefits and quality of wine raw materials while for service quality which is the main priority is improved on wine product marketing attributes and wine product offering attributes.